Respect the spindle : spin infinite yarns with one amazing tool - Franquemont, Abby, 1972- (Interweave Press, 2009)
Why would modern spinners choose to make yarn with a prehistoric tool? Abby Franquemont explores one of the world's most productive, versatile, and convenient devices and teaches readers to make yarn using it.